Management of environmental health issues for the 2004 Athens Olympic Games: is enhanced integrated environmental health surveillance needed in every day routine operation? - Chervoni Julia; Kalivitis Isidiros; Vousoureli Anastasia; Kapoula Christina; Vaitsi Vasiliki; Mouchtouri Varvara; Hadjichristodoulou Christos; Papastergiou Panagiotis; Vasilogiannakopoulos Antonios; Daniilidis Vasilis D; Kremastinou Jenny (BMC, 2006)
Abstract Background Management of environmental health issues is an integral part of public health systems. An active integrated environmental health surveillance and response system was developed for the Athens Olympics to monitor and prevent exposure to environmental hazards. The potential for permanent implementation of the program was examined. Methods The environmental health surveillance and response system included standardization, computerization and electronic transmission of data concerning environmental inspections of 17 site categories (restaurants, swimming pools etc) of public health interest, drinking and recreational water examinations and suggested corrective actions. The Olympic Planning Unit integrated and centrally managed data from 13 public health agencies, recommended, supervised and coordinated prompt corrective actions. Methods used to test the effectiveness of the program were the assessment of water quality test and inspection results trends over time using linear regression and epidemiological surveillance findings. Results Between January 2003 and September the 30th, 2004, 196 inspectors conducted 8562 inspections, collected 5024 water samples and recommended 17 027 corrective actions. In 10 cruise ships used as floating hotels inspectors conducted 10 full inspections, 2 re-inspections, and 27 follow-up inspections. Unsatisfactory inspection results (r = 0.44, p < 0.0001) and positive water quality tests (r = 0.39, p < 0.001) presented an overall decrease trend over time. In August, 2003, an outbreak of salmonellosis was linked to a hotel restaurant which accommodated athletes during a test event. Conclusion Lessons learned for future events include timely implementation and installation of communication processes, and rapid and coordinated response to unsatisfactory inspection results. Routine national programs need to adopt enhanced environmental health surveillance aimed at public health decision-making, but with a different perspective.